High fidelity of sea turtles to their foraging grounds revealed by satellite tracking and capture-mark-recapture: New insights for the establishment of key marine conservation areas. (October 2020) - Siegwalt, Flora; Benhamou, Simon; Girondot, Marc; Jeantet, Lorène; Martin, Jordan; Bonola, Marc; Lelong, Pierre; Grand, Clément; Chambault, Philippine; Benhalilou, Abdelwahab; Murgale, Céline; Maillet, Thomas; et al.
Abstract: Movement ecology studies are essential to protect highly mobile threatened species such as the green turtle ( Chelonia mydas ), classified as an endangered species by the IUCN. In 2019, the South Atlantic subpopulation has been downlisted to 'Least Concern', but the maintenance of this status strongly relies on the pursuit of research and conservation, especially on immatures, which contribute to the demographic renewal of this subpopulation. Identifying marine areas used by immatures is therefore crucial to implement efficient measures for the conservation of sea turtles in the Caribbean. We analysed data of capture-mark-recapture of 107 (out of 299) immatures recaptured at least once in Martinique, and satellite tracked 24 immatures to investigate their site fidelity and habitat use. Our results revealed a strong fidelity to foraging grounds, with mean residence times higher than 2 years, and with a high degree of affinity for specific areas within the coastal marine vegetation strip. Home ranges (95% kernel contour) and core areas (50% kernel contour) varied from 0.17 to 235.13 km 2 (mean ± SD = 30.73 ± 54.34 km 2 ) and from 0.03 to 22.66 km 2 (mean ± SD = 2.95 ± 5.06 km 2 ), respectively. Our findings shed light on a critical developmental area for immature green turtles in the French West Indies, and should help to refine Regional Management Units and reinforce the cooperative network aiming at ensuring conservation of the species at international scale. Highlights: Green turtle residency in Martinique was estimated between 2 and 74 years. Strong site fidelity with home ranges overlapping with coastal seagrass beds Immature are sedentary until they approach sexual maturity, then they migrate. Martinique island is a foraging hotspot for immature green turtles in the Caribbean.